2016
DOI: 10.1111/acel.12500
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐amyloid 1‐42 monomers, but not oligomers, produce PHF ‐like conformation of Tau protein

Abstract: SummaryThe mechanistic relationship between amyloid β1‐42 (Aβ1‐42) and the alteration of Tau protein are debated. We investigated the effect of Aβ1‐42 monomers and oligomers on Tau, using mice expressing wild‐type human Tau that do not spontaneously develop Tau pathology. After intraventricular injection of Aβ1‐42, mice were sacrificed after 3 h or 4 days. The short‐lasting treatment with Aβ monomers, but not oligomers, showed a conformational PHF‐like change of Tau, together with hyperphosphorylation. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…Mice expressing human tau, hTau mice (Mapt tm1(EGFP)Klt Tg(MAPT) 8cPdav/J; #004808, The Jackson Laboratory, Bar Harbor, ME, USA), were crossed with tau knock-out (KO) mice (Mapt tm1(EGFP)Klt /J; #004779, Jackson Laboratory), to obtain pregnant females carrying hTau fetuses [21] . The mice were genotyped by PCR assay as described by Manassero and colleagues [22] . They were maintained on a Swiss Webster/129/SvJae/C57BL/6 background [21] , and kept on a 12 h light/dark cycle with food and water available ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…Mice expressing human tau, hTau mice (Mapt tm1(EGFP)Klt Tg(MAPT) 8cPdav/J; #004808, The Jackson Laboratory, Bar Harbor, ME, USA), were crossed with tau knock-out (KO) mice (Mapt tm1(EGFP)Klt /J; #004779, Jackson Laboratory), to obtain pregnant females carrying hTau fetuses [21] . The mice were genotyped by PCR assay as described by Manassero and colleagues [22] . They were maintained on a Swiss Webster/129/SvJae/C57BL/6 background [21] , and kept on a 12 h light/dark cycle with food and water available ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…All values were presented as mean ± standard error (SEM). Means were compared by one or two-way analysis of variance (ANOVA) with Bonferroni as a post hoc test (Manassero et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…We investigated whether Aβ 42 could modify the conformation and/or the phosphorylation of tau protein to render it more prone to aggregate [ 44 ]. Previous data reported three major mechanisms through which Aβ peptides may induce tau aggregation: 1) Aβ phosphorylates tau through the activation of specific kinases and this event alters the ability of tau to bind tubulin [ 45, 46 ]; 2) Aβ interferes with proteasomal degradation of tau, thus increasing the free-state of the protein [ 47 ]; 3) Aβ aggregates exert a nucleation effect on tau [ 3, 4 ].…”
Section: Aβ 42 Monomers Vs Oligomers On Tau Aggregmentioning
confidence: 99%
“…We demonstrated that Aβ 42 monomers, but not oligomers, intraventricularly injected in mice expressing wild type human tau, produce a pathological conformational change of tau protein [ 44 ]. In the same experimental model, we also found that monomers induce phosphorylation of pathological tau epitopes activating GSK3β, JNK, and ERK kinases and that the inhibition of these kinases rescues the tau conformational change [ 44 ]. Finally, we investigated whether the observed modification of tau mediated by Aβ monomers could be ascribed to an increase of tau protein levels.…”
Section: Aβ 42 Monomers Vs Oligomers On Tau Aggregmentioning
confidence: 99%
See 1 more Smart Citation